Preparation method and application of amorphous ruthenium oxide catalyst

The development of mesoporous amorphous RuO2 nanosheets addresses the limitations of existing electrocatalytic sulfide oxidation methods by achieving high yield and selectivity, enabling efficient and scalable production of sulfoxides.

CN119243214APending Publication Date: 2025-01-03NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411471289.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing electrocatalytic sulfide oxidation methods for sulfoxide production suffer from low selectivity, low Faradaic efficiency, and poor substrate scalability, limiting their industrial application.

Method used

A method for preparing mesoporous amorphous RuO2 nanosheets (a-RuO2) as a catalyst, which promotes the dissociation of water molecules at low potentials to generate surface oxygen active species for selective sulfide oxidation.

Benefits of technology

a-RuO2 achieves ultra-high yield (>99%) and selectivity (99%) with Faradaic efficiency (98%) for sulfide oxidation, expanding substrate range and enabling gram-scale reactions, thus enhancing practical application in organic chemical production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243214A_ABST
    Figure CN119243214A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an amorphous ruthenium oxide catalyst, and the prepared amorphous ruthenium oxide catalyst (a-RuO2) can promote dissociation of water molecules under low potential to obtain surface oxygen active species, so as to excellently catalyze selective oxidation of sulfides. By taking methyl phenyl sulfide (MPS) as a model substrate, the a-RuO2 can realize super-high yield (gt; 99%), selectivity (99%) and Faraday efficiency (98%), and the voltage relative to RHE is 1.85 V. In addition, the practical application of electrochemistry in the production of organic chemicals can be further promoted by expanding the substrate range and carrying out gram-level reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts, and in particular to a preparation method of an amorphous ruthenium oxide catalyst and application thereof. Background Art

[0002] Sulfides are important oxygen-containing organosulfur compounds that are often used as versatile reaction intermediates in organic synthesis and can also play an important role as drugs, pesticides and fragrances. Selective oxidation of sulfides is one of the most direct and effective methods for the synthesis of sulfoxides. However, traditional synthetic methods usually require additional oxidants, such as chemical oxidants (H2O2, t-BuOOH, HNO3, NaOCl, etc.), inorganic oxides (MnO2 or Fe(NO3)3), and oxygen (O2), which leads to a series of problems such as low atom utilization, explosion hazard, over-oxidation and poor substrate scalability. Undoubtedly, a more efficient strategy driven by "green oxygen" is urgently needed to meet the production requirements of green chemistry and chemical compatibility.

[0003] Electrochemical selective oxidation methods utilize renewable electricity to produce the desired chemicals and are therefore a compelling alternative to conventional sulfide oxidation to sulfoxide methods. Direct electrochemical oxidation and redox-mediated electrochemical oxidation methods were initially used for the selective oxidation of sulfides to produce sulfur oxides. In the currently reported electrocatalytic sulfide oxidation to sulfoxide processes, the mainstream catalysts include precious metal catalysts or hydroxide catalysts, etc. These catalysts have low selectivity, low yield, low Faraday efficiency, and poor substrate scalability for electrocatalytic sulfide oxidation, which restricts their industrial application.

[0004] Currently, the catalyst system for the electrocatalytic oxidation of sulfide to prepare sulfoxide pays little attention to the production efficiency and practicality of actual applications. The main research direction is focused on improving the performance of one-pot reactions, without extending to the stability of the catalytic system, the amplification of reactions, and the reaction scalability of various nitro compounds.

[0005] Therefore, it is necessary to design a catalyst with superior performance to achieve high selectivity, high Faradaic efficiency, and substrate scalability for the direct oxidation of a variety of sulfide substrates. Summary of the invention

[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing an amorphous ruthenium oxide catalyst in view of the shortcomings of the prior art, which is a mesoporous amorphous RuO2 nanosheet (named a-RuO2), which can promote the dissociation of water molecules at low potentials to obtain surface oxygen active species, thereby excellently catalyzing the selective oxidation of sulfides.

[0007] In order to solve the above technical problems, the present invention discloses a method for preparing an amorphous ruthenium oxide catalyst, comprising the following steps:

[0008] (1) dissolving ruthenium acetylacetonate and potassium bromide in an ethanol aqueous solution, drying at 60 to 150° C. after the mixture is completely dissolved, and then grinding the obtained powder;

[0009] (2) The powder obtained in step (1) is heated and calcined in a muffle furnace, and the calcined powder is washed with water and ethanol, and dried at 75° C.-90° C. to obtain amorphous ruthenium oxide.

[0010] Wherein, in step (1), the mass ratio of ruthenium acetylacetonate to potassium bromide is 1:10 to 2:1.

[0011] The calcination conditions in step (2) are: heating to 265-345° C. and maintaining at this temperature for 60-120 minutes.

[0012] In a specific embodiment, an amorphous ruthenium oxide catalyst is prepared according to the following steps: 400 mg of ruthenium acetylacetonate (Ru(acac)3) and 750 mg of potassium bromide are dissolved in a mixture of 125 ml of water and 125 ml of ethanol. After the solution is completely dissolved, it is dried at 110°C, and then the obtained powder is ground and then heated to 285°C in a muffle furnace and maintained at 285°C for 90 minutes. The calcined powder is washed with water and ethanol, and dried at 80°C to obtain amorphous ruthenium oxide.

[0013] The present invention further proposes the use of the amorphous ruthenium oxide catalyst prepared by the above preparation method in the electrocatalytic preparation of sulfoxide compounds from sulfide compounds.

[0014] Wherein, the sulfide compound has the following structural formula:

[0015] Wherein, R1 is any one of the aromatic groups, and R2 is any one of the alkane groups.

[0016] The specific reaction process is:

[0017]

[0018] In some specific embodiments, the thioether compound is methyl phenyl thioether or a thioether derivative whose para-substituent is -F, -Cl, -Br, or -OCH3.

[0019] In another embodiment, the thioether compound is a thioether derivative containing a phenyl group, an aliphatic substituent or a benzyl group.

[0020] At the same time, for drug precursor molecules, high yield and selectivity can still be obtained under the condition of electrolysis of 2F / mol.

[0021] Beneficial effects: The mesoporous amorphous RuO2 nanosheets (named a-RuO2) prepared in this application can promote the dissociation of water molecules at low potentials to obtain surface oxygen active species, thereby excellently catalyzing the selective oxidation of sulfides. Using methyl phenyl sulfide (MPS) as a model substrate, a-RuO2 can achieve ultra-high yield (>99%), selectivity (99%) and Faradaic efficiency (98%), with a voltage of 1.85V relative to RHE. In addition, expanding the substrate range and performing gram-scale reactions will further promote the practical application of electrochemistry in the production of organic chemicals. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 a is the flow chart of preparation of mesoporous amorphous RuO2 catalyst;

[0023] Figure 1 b is the XRD pattern of c-RuO2 and a-RuO2;

[0024] Figure 1 c is the Raman image of c-RuO2 and a-RuO2;

[0025] Figure 1 d is the spherical aberration corrected HAADF-STEM image of a-RuO2, and the inset shows the selected electron diffraction pattern of a-RuO2;

[0026] Figure 1 e is the spherical aberration corrected HAADF-STEM image of c-RuO2, and the inset shows the selected electron diffraction pattern of c-RuO2;

[0027] Figure 1 f is the TEM image of c-RuO2;

[0028] Figure 1 g is the SEM image and element mapping results of a-RuO2;

[0029] Figure 1 h is the AFM image of a-RuO2;

[0030] Figure 1 i is the Ru 3p XPS analysis of c-RuO2 (upper) and a-RuO2 (lower);

[0031] Figure 1 j is the XANES spectra of Ru K edge of a-RuO2, c-RuO2 and standard samples;

[0032] Figure 2a is a reaction flow chart of preparing MPSO by oxidizing MPS catalyzed by a-RuO2 or c-RuO2 as an anode catalyst;

[0033] Figure 2 b is the linear sweep voltammetry (LSV) of a-RuO2 and c-RuO2 in 0.1MTMAP and 10% water / MeCN;

[0034] Figure 2 c is the Faradaic efficiency and selectivity of a-RuO2 and c-RuO2 at different potentials in 25 mM MPS and 0.1 M TMAP and 10% water / MeCN solution, and the electrolysis time is 3 hours;

[0035] Figure 2 d is the relationship between the charge tracking experiment of MPS oxidation and RHE at a potential of 1.85 V;

[0036] Figure 2 e is the recovery performance of the a-RuO2 electrolysis system;

[0037] Figure 2 f is a gram-scale reaction flow chart, the reaction solution is 15 ml (10% water / MeCN), 0.25 M TMAP and 1.285 g MPS, and the electrolysis potential is 2.6 V vs. RHE;

[0038] Figure 2 g is the comparison of yield and Faradaic efficiency with other heterogeneous electrocatalytic reactions. DETAILED DESCRIPTION

[0039] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0040] Example 1 Preparation of mesoporous amorphous RuO2 (a-RuO2) nanosheets.

[0041] Catalyst preparation process Figure 1 As shown in a. 400 mg of ruthenium acetylacetonate (Ru(acac)3) and 750 mg of potassium bromide were dissolved in a mixture of 125 ml of water and 125 ml of ethanol. After the solution was completely dissolved, it was dried at 110°C, and then the obtained powder was ground and then heated to 285°C in a muffle furnace and kept at 285°C for 90 minutes. The calcined powder was washed with water and ethanol and dried at 80°C to obtain amorphous ruthenium oxide. The prepared sample was characterized, and the results are shown in Figure 1 As shown in b-1g, the common commercial electro-oxidation catalyst ruthenium oxide catalyst c-RuO2 was purchased from Tim (Beijing) New Materials Technology Co., Ltd.

[0042] The crystal morphology was characterized by X-ray diffraction (XRD), as shown in Figure 1 b. a-RuO2 has no obvious diffraction peaks, which indicates that the material has long-range disorder, consistent with typical amorphous materials, while c-RuO2 has sharp diffraction peaks, which correspond to Rutile phase RuO2 (JCPDS#43-1027), indicating that it has high crystallinity. Raman spectroscopy results further show that the characteristic peaks of a-RuO2 and c-RuO2 are concentrated at 512cm -1 、627cm -1 and 693cm -1 ,like Figure 1 c. Significantly, the Raman characteristic peak of a-RuO2 is weaker and flatter than that of c-RuO2, indicating that it has lower symmetry and short-range order, and is characterized by amorphous features. More detailed microscopic crystal information was further investigated by aberration-corrected high-angle annular dark field scanning transmission electron microscopy (AC-HAADF-STEM). Figure 1 d and its inset, no obvious crystal fringes of a-RuO2 are observed, and the corresponding selected area electron diffraction (SAED) shows a halo-like pattern, confirming the amorphous nature of a-RuO2. In contrast, c-RuO2 has obvious crystal lattice fringes corresponding to the (110) and (101) crystal planes of RuO2, as shown in Figure 4. Figure 1 As shown in Figure e, this proves the orderliness of its atomic arrangement, which is consistent with the XRD results. The microstructure of a-RuO2 was further characterized by scanning electron microscopy (SEM), as shown in Figure 5. Figure 1 g. a-RuO2 is in the form of multi-layer stacked nanosheets. Elemental analysis shows that Ru and O are evenly distributed on the nanosheets, and no other heterogeneous elements are found. Atomic force microscopy (AFM) observed that the thickness of a-RuO2 is 65.8 nanometers and the surface is relatively flat, as shown in Figure 2. Figure 1 h. XPS shows the elemental state and electronic structure of a-RuO2 and c-RuO2. Figure 1 i shows the high-resolution XPS of Ru 3p. The Ru 2p3 / 2 peak position of a-RuO2 and c-RuO2 is both located at 462.5eV, with no significant shift, indicating that the Ru element mainly exists in the +4 oxidation state, and the proportion of the two samples is similar. In order to further verify the unique valence state and electronic structure of a-RuO2, X-ray absorption spectroscopy tests were also performed. Figure 1 As shown in Figure j, the white line region of the Ru K-edge X-ray absorption near-edge structure (XANES) spectrum of a-RuO2 shows that its oxidation state is only slightly lower than +4, indicating that its valence composition is similar to that of RuO2, which is consistent with the XPS results.

[0043] Example 2 Application of mesoporous amorphous RuO2 nanosheets in catalytic oxidation of methyl phenyl sulfide (MPS).

[0044] The a-RuO2 or c-RuO2 prepared in Example 1 was used as an anode catalyst to catalyze the oxidation of MPS. The reaction conditions were: 20 mL of solution (10% H2O / MeCN), 0.1 M tetrabutylammonium perchlorate as a supporting electrolyte, 1 mmol of anisole added or not, 0.5 mg of ruthenium oxide catalyst loaded on a 1*2 cm carbon paper electrode as an anode, a platinum sheet electrode as a cathode, and Ag / AgCl as a reference electrode. LSV( Figure 2 b), without adding MPS, the anode reaction is OER, and the ability of a-RuO2 to electrolyze water is significantly better than that of c-RuO2. After adding MPS, compared with the corresponding OER curve, the starting potential of a-RuO2 or c-RuO2 decreases and the current density increases, which indicates that MPS oxidation participates in the anode reaction. Among them, the starting potential of a-RuO2 catalyzing MPS oxidation is only 1.25V, which is about 400mV higher than that of c-RuO2, indicating that a-RuO2 has excellent sulfide oxidation performance. In order to further explore the performance difference between the two, we used constant potential electrolysis at different potentials to evaluate the conversion rate of MPS, using a-RuO2 or c-RuO2 prepared in Example 1 as an anode catalyst to catalyze MPS oxidation, reaction conditions: 20mL solution (10% H2O / MeCN), 0.1M concentration of tetrabutylammonium perchlorate as a supporting electrolyte, 1mmol of anisole, 0.5mg of ruthenium oxide catalyst loaded on a 1*2cm carbon paper electrode as an anode, a platinum sheet electrode as a cathode, Ag / AgCl as a reference electrode, electrolysis at different potentials for 3 hours. Figure 2 As shown in Figure c, the selectivity and FE (Faraday efficiency) of MPS oxidation catalyzed by a-RuO2 first increase and then decrease with the increase of potential, and are better than c-RuO2 under all conditions. The performance is best at 1.85V to RHE, reaching about 99% selectivity and 98% FE, while -RuO2 can only reach about 78% selectivity and 78% FE at 2.05V to RHE. The effective current density of a-RuO2 and c-RuO2 was calculated based on FE. According to the above comparative experiment, a-RuO2 was selected as the anode catalyst to carry out the complete conversion experiment of MPS oxidation, and a-RuO2 or c-RuO2 prepared in Example 1 was used as the anode catalyst to catalyze the MPS oxidation, and the reaction conditions were: 20mL solution (10% H2O / MeCN), 0.1M concentration of tetrabutylammonium perchlorate as the supporting electrolyte, 1mmol of anisole thioether was added, 0.5mg of ruthenium oxide catalyst was loaded on a 1*2cm carbon paper electrode as the anode, a platinum sheet electrode as the cathode, and Ag / AgCl as the reference electrode, and 50, 100, 150, and 200C of electricity were electrolyzed respectively. Figure 2 As shown in Figure d, the reduction of MPS and the generation of MPSO are linearly correlated with the increase in charge, indicating that the reaction always maintains a high FE and stable selectivity, while phenylsulfone peroxide as a by-product only appears in the late stage of the reaction, accounting for only about 2%. It was calculated that the MPS conversion rate of a-RuO2 at 1.85V vs. RHE was 97.3%, the MPSO selectivity was 98.8%, and the FE was 95.8%. In order to study the stability of the catalyst, the MPS electrooxidation reaction catalyzed by a-RuO2 was repeated. As shown in Figure d, the reduction of MPS and the generation of MPSO are linearly correlated with the increase in charge, indicating that the reaction always maintains a high FE and stable selectivity, while phenylsulfone peroxide only appears as a by-product in the late stage of the reaction, accounting for only about 2%. Figure 2 As shown in Figure e, after 10 cycles, the reaction parameters of a-RuO2 remained at a high level, and the performance hardly decreased, indicating that it has good stability. In order to further demonstrate the practicability of this method, we carried out gram-scale amplification, using a-RuO2 or c-RuO2 prepared in Example 1 as an anode catalyst to catalyze the oxidation of MPS. The reaction conditions were: 20 mL of solution (10% H2O / MeCN), 0.1 M concentration of tetrabutylammonium perchlorate as the supporting electrolyte, 10 mmol of anisole thioether, 0.5 mg of ruthenium oxide catalyst loaded on a 1*2 cm carbon paper electrode as the anode, a platinum sheet electrode as the cathode, and Ag / AgCl as the reference electrode. The electrolysis was carried out at 2.6 V relative to RHE for 2020C of electricity. , as Figure 2 f. After appropriately increasing the electrolyte concentration (0.25M n-Bu4NClO4) and the potential (2.6V vs.RHE), the gram-scale experiment was completed in only 13.66 hours, with an MPSO yield of 92% and a FE of 91%. Figure 2 g shows the comparison between the electrochemical method and the literature reports (Table 1). Although the yield of most studies can reach about 90%, the FE is at a low level. This work significantly improves the FE while maintaining a high yield, indicating that this method has a high reaction selectivity. At the same time, compared with the reaction rate of the research work, the catalyst synthesized in this work is in a leading position compared with the existing homogeneous or heterogeneous electrocatalysis.

[0045] Table 1

[0046]

[0047] In addition, we also selected other types of thioether compounds as substrates to verify the versatility of this method. We electrochemically oxidized 11 other types of thioether compounds. Similar to MPS, a-RuO2 showed good reaction selectivity after the addition of the substrate. Subsequently, constant potential electrolysis was carried out at a potential of 1.85 V relative to RHE, as shown in Table 2. For thioether derivatives with para-substituents of -F, -Cl, -Br, and -OCH3 (2c-2f), their yields and FE were relatively ideal; thioether derivatives containing phenyl, aliphatic substituents, and benzyl (2b, 2j, 2k) could also be smoothly oxidized to sulfoxides, indicating that this method has good functional group tolerance. The steric hindrance caused by the change in the position of the substituent (2d, 2g-2k) also had no obvious effect on the reaction results. For alkyl linear thioethers (2i), the yield of sulfoxides was as high as 95% under these conditions, and there was no obvious peroxidation reaction. For drug precursor molecules (such as 2j. albendazole, 2k. omeprazole, 2l. sulindac, 2m. pantoprazole, 2n. rabeprazole, 2o fipronil), high yields and selectivities can still be obtained under the condition of applying twice the theoretical conversion amount. The specific results are shown in Table 1.

[0048] Table 2

[0049]

[0050]

[0051]

[0052] Example 3 Catalytic properties of the catalyst under different electrolytes, sulfide concentrations and voltages.

[0053] The amorphous ruthenium oxide a-RuO2 prepared in Example 1 was subjected to batch electrolysis measurement and divided into the following groups:

[0054] (1) 15 mL of electrolyte (0.1 M tetrabutylammonium perchlorate as electrolyte) was added to a magnetically stirred single-cell electrolytic cell, and anisole (50 mM) was added. 144.8 C of electricity was electrolyzed at a potential of 1.85 V vs. RHE. After the reaction, the cathode solution was collected for product analysis. The results showed that high selectivity (99%), Faraday efficiency (95%) and yield (98%) of anisole sulfoxide could be achieved.

[0055] (2) 15 mL of electrolyte (0.1 M tetrabutylammonium perchlorate as electrolyte) was added to a magnetically stirred single-cell electrolytic cell, and anisole (25 mM) was added. 73 C of electricity was electrolyzed at a potential of 1.85 V vs. RHE. After the reaction, the cathode solution was collected for product analysis. The results showed that high selectivity (98%), Faraday efficiency (97%) and yield (97%) of anisole sulfoxide could be achieved.

[0056] (3) 15 mL of electrolyte (0.1 M tetrabutylammonium perchlorate as electrolyte) was added to a magnetically stirred single-cell electrolytic cell, and anisole (50 mM) was added. 144.8 C of electricity was electrolyzed at a potential of 1.95 V vs. RHE. After the reaction, the cathode solution was collected for product analysis. The results showed that high selectivity (98%), Faraday efficiency (98%) and yield (98%) of anisole sulfoxide could be achieved.

[0057] (4) 30 mL of electrolyte (0.1 M tetrabutylammonium perchlorate as electrolyte) was added to a magnetically stirred single-cell electrolytic cell, and anisole (50 mM) was added. 289.6 C of electricity was electrolyzed at a potential of 1.85 V vs. RHE. After the reaction, the cathode solution was collected for product analysis. The results showed that high selectivity (96%), Faraday efficiency (95%) and yield (95%) of anisole sulfoxide could be achieved.

[0058] (5) 15 mL of electrolyte (0.2 M tetrabutylammonium perchlorate as electrolyte) was added to a magnetically stirred single-cell electrolytic cell, and diphenyl sulfide (50 mM) was added. 144.8 C of electricity was electrolyzed at a potential of 1.85 V vs. RHE. After the reaction, the cathode solution was collected for product analysis. The results showed that high selectivity (98%), Faraday efficiency (97%) and yield (97%) of benzyl sulfoxide could be achieved.

[0059] The present invention provides a method for preparing an amorphous ruthenium oxide catalyst and its application. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing an amorphous ruthenium oxide catalyst, characterized in that: The steps include: Dissolve ruthenium acetylacetonate and potassium bromide in an ethanol aqueous solution, dry at 60-150°C after the solution is completely dissolved, and grind the obtained powder; The powder obtained in step (1) is heated and calcined in a muffle furnace, and the calcined powder is washed with water and ethanol, and dried at 75° C.-90° C. to obtain amorphous ruthenium oxide.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of ruthenium acetylacetonate to potassium bromide is 1:10 to 2:

1.

3. The preparation method according to claim 1, characterized in that: The calcination conditions are: heating to 265-345°C and maintaining at this temperature for 60-120 minutes.

4. The preparation method according to claim 1, characterized in that: The method comprises the following steps: dissolving 400 mg of ruthenium acetylacetonate and 750 mg of potassium bromide in a mixture of 125 ml of water and 125 ml of ethanol; drying the solution at 110°C after the solution is completely dissolved; grinding the obtained powder; and subsequently heating the powder to 285°C in a muffle furnace and maintaining the powder at 285°C for 90 minutes; washing the calcined powder with water and ethanol, and drying the powder at 80°C to obtain amorphous ruthenium oxide.

5. Use of the amorphous ruthenium oxide catalyst prepared by the preparation method according to any one of claims 1 to 3 in the electrocatalytic preparation of sulfoxide compounds from sulfide compounds.

6. The use according to claim 4, characterized in that: The thioether compound has the following structural formula: , wherein R1 is any one of the aromatic groups, and R2 is any one of the alkane groups.